IMPLEMENTASI PROGRAM PENANGGULANGAN TUBERKULOSIS DI KABUPATEN SEMARANG TAHUN 2013 - Setyawan, Aditya David Bagus; Rengga, Aloysius; Rostyaningsih, Dewi (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
Indonesia is at the fourth position of the highest tuberculosis sufferers in the world after India, China, and South Africa. Tuberculosis prevention in Indonesia has been done in accordance to Tuberculosis Prevention National Program that was proclaimed by Health Ministry of Republic Indonesia for all Regencies and Cities. By deciding 70% target invention from total estimation and curing minimum 85% from total patient that are positively tuberculosis. However, implementation tuberculosis prevention program in Semarang Regency in invention amount has not reached national target. Invention amount of tuberculosis patients that are gained only reachs 24,42%, and the recovery level reachs 94,08%. The purpose of this research is to know how implementation tuberculosis prevention program that is done by Semarang Regency Health Department by using indicator effectiveness implementation policy that consist of: policy accuracy, implementer accuracy, target accuracy, environment accuracy, process accuracy, and also the factors and implementation of tuberculosis prevention program resistor. The research uses a theory of George C. Edward III by Top Down approachment. This research focuses on implementer program in implementing tuberculosis prevention program by noticing its communication factor, resources, disposition, and birocracy structure. The research uses descriptive qualitative research method. The result indicates that the implementation of tuberculosis prevention program in Semarang Regency is not effective yet, it happened because some implementation effectiveness indicators has not been fulfilled enough. On the other hand, there are several factors that resist the implementation of tuberculosis prevention program in Semarang Regency. It is needed addition of competent human resources in tuberculosis prevention field and involve department society strategic.